2017
DOI: 10.1177/0001699317717320
|View full text |Cite
|
Sign up to set email alerts
|

Secular and religious volunteering among immigrants and natives in Denmark

Abstract: In the last decades, Western societies have witnessed large scale migration from the Global South. This large-scale migration has brought about important challenges in securing the social, civic, and political integration of non-Western immigrants into Western societies. The previous research suggests that participation in volunteering within civil society can serve as a 'stepping stone' towards integration for immigrants. However, the previous research has shown marked gaps in the propensity to participate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Similar to findings in other countries (e.g., Carabain and Bekkers, 2011 in the Netherlands; Osili and Xie, 2009, in the US; Qvist, 2017, in Denmark; Voicu, 2014), our study first confirmed that immigrants in Germany engage less in volunteering than native-born individuals. This finding is particularly robust in our analysis given the use of a propensity score-matched sample.…”
Section: Discussion and Policy Implicationssupporting
confidence: 89%
“…Similar to findings in other countries (e.g., Carabain and Bekkers, 2011 in the Netherlands; Osili and Xie, 2009, in the US; Qvist, 2017, in Denmark; Voicu, 2014), our study first confirmed that immigrants in Germany engage less in volunteering than native-born individuals. This finding is particularly robust in our analysis given the use of a propensity score-matched sample.…”
Section: Discussion and Policy Implicationssupporting
confidence: 89%
“…Research shows that Norwegian adults of Asian or African immigrant backgrounds are less likely to participate in political elections (Bergh, 2016; Bergh et al, 2014) or voluntary organizations (Eimhjellen and Segaard, 2010; Wollebæk and Sivesind, 2010) than the general population. A similar pattern is evident in other Nordic countries (Bhatti et al, 2014; Qvist, 2018; Svedberg et al, 2010).…”
Section: Introductionsupporting
confidence: 79%
“…Citizens of immigrant descent constitute a growing share of the populations in most western democracies, thereby increasing their political significance. Compared to the majority population, however, immigrants coming from Asia and Africa, in particular, are less likely to engage in politics (Bergh et al, 2014; Bhatti et al, 2014; Heath and Khan, 2012; Qvist, 2018; Svedberg et al, 2010). As far back as the 1960s, empirical studies have shown that members of voluntary associations are more politically active and interested than non-members (Almond and Verba, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its aim was to examine their views on the way children in Greece experience the consequences of the economic downturn and the degradation of their well-being. The participants of this study were involved in "religious volunteering" as they were all taking part in the organization of the parish soup kitchens and linked their participation with religious norms and values (Qvist, 2017). This study was based on the assumption that one can only indirectly approach the way the children perceive the impact of the crisis on their lives in the Greek family welfare model.…”
Section: What Is the Case In Greece?mentioning
confidence: 99%